A framework for positioning analysis: From identifying to analyzing (pre)positions in narrated story lines. (November 2021) - Kayi-Aydar, Hayriye
Abstract: Developed as a theoretical framework, Positioning Theory (e.g., Davies & Harré, 1990, 1999) focuses on how individuals are positioned in interactions and narratives as micro-level identities are constructed, projected, or negotiated. While the theory has been applied widely to studies across disciplines, I argue that a comprehensive and systematic analytic framework for positioning analysis that can be applied to discourses of educational contexts has not been offered yet. This paper offers an analytic framework that can be used in identifying and analyzing prepositioning and positions in narrated story lines. The framework consists of three layers of analysis: a) story lines and positions, b) relational positioning categories, and c) social consequences. Such a comprehensive framework is necessary in establishing trustworthiness in positioning studies, guiding researchers who wish to engage in positioning analysis, and understanding and analyzing identity work more thoroughly in narrated story lines. The current paper first introduces and explains this framework and then illustrates how it is applied to narrated story lines collected in the form of narrative frames (Barkhuizen, 2014) in a study on teacher identity.